Research on Strait Crossing Solution of Submerged Floating Tunnel (Underwater Continuous Girder Bridge). (2016) - Wang, Xueji; Liu, Gang
Abstract: On the background of a certain strait channel construction abroad, based on the research of domestic strait crossing solution, a tunnel crossing solution (submerged floating tunnel or underwater continuous girder bridge) is designed, which foundation is ordinary Column Piers and Main beam is for vehicle passing. It is similar to Ordinary continuous girder bridge which is relatively simple. This paper introduced the characteristic and technological difficulty of this solution, discussing its feasibility.